Effects of Player's Participation Patterns on Economic Performance of Entertainment Shopping Website - Jin Li; Kwok Fai Tso (International Journal of Informatics and Information Systems, 2019)
Online pay-per-bid auction is a new entertainment shoppingformat with a mechanism that integrates the characteristics of traditional e-commerce, online auctions, lotteries and games. Previous researches have shown this auction format possesses high variances and uncertainties. However, research on the players' participation patterns and performance is rare. In this study, we attempt to study how players' participation patterns can affect both their own and websites' performance. An empirical study with data collected from an online pay-per-development website with 5,650players' participation behavior is performed. Particularly, the role of players preference is also explored through a cluster analysis of their historical participations. Multiple linear regression models and regression models with beta distributions are used for hypothesis testing. Findings confirm that players participation performance and websites revenue strongly associated with the players participation patterns. The results show that (1) players with longer lifetime perform better and contribute more revenue to the website; (2) players participating in more auctions show worse performance and websites obtain more revenue from them; and (3) players with a strong preference behave more irrationally and website benefits more from them. Both theoretical and managerial implications are discussed.